Pengaruh Kompetensi Independensi dan Motivasi Auditor terhadap Kualitas Audit Internal - Jefry Naldi; Halmawati Halmawati (Universitas Negeri Padang, 2021)
This study aims to determine the extent of: The influence of competence, independence, and auditor motivation on the quality of internal audit at BUMS and BUMN in Padang City. The population in this study are private companies and state-owned companies in the city of Padang which have several internal auditors in the company. The sample in this study were all internal auditors in private companies and state-owned companies in the city of Padang. The data source is primary data. The technique of studying data with a questionnaire. The data analysis technique is multiple linear regression. The results showed that: (1) Competence has a positive effect on the quality of internal audit, where the coefficient β of competence is positive at 0.092 and the t value is 1.791 with a significance value of 0.048> 0.05. (2) Independence has no significant effect on the quality of internal audit, where the independence β coefficient is negative at 0.007 and the t value is -0.135 with a significance value of 0.893> 0.05. (3) Auditor motivation has no effect on the quality of internal audit, where the coefficient β of motivation is negative at 0.058 and the t value - 0.761 with a significance value of 0.449> 0.05.